Pengaruh Model Pembelajaran Flipped Classroom Terhadap Motivasi Belajar IPAS Pada Siswa Kelas V SDN Genukwatu IV Ngoro Jombang - Tunnaja, Aulia Safina; Susilo, Claudya Zahrani (Prodi Pendidikan Guru Sekolah Dasar, 2024)
Education plays an important role in the formation of individual character and abilities, especially in children at the elementary school level. This study explores the effect of the Flipped Classroom learning model on the motivation to learn Natural and Social Sciences (IPAS) in grade 5 students at SDN Genukwatu IV Ngoro Jombang. Flipped Classroom changes the traditional learning paradigm by moving the delivery of material to home through videos or reading materials, while concept mastery activities are carried out in class. This study uses a quantitative approach with a pre-post experimental design, comparing the experimental group that implemented Flipped Classroom with the control group that used conventional methods. Data were collected through a valid and reliable learning motivation questionnaire. The results are expected to provide insight into the effectiveness of this model in improving student learning motivation, as well as its implications for the application of innovation in education, especially in rural areas that face unique challenges in learning. This study aims to improve the quality of education at the elementary level by understanding the effect of learning models on student motivation.